Biocontrol Activity of Volatile-Producing Bacillus megaterium and Pseudomonas protegens Against Aspergillus and Penicillium spp. Predominant in Stored Rice Grains: Study II - Mannaa, Mohamed (Mycobiology, 2018)
In our previous studies, Bacillus megaterium KU143, Microbacterium testaceum KU313, and Pseudomonas protegens AS15 have been shown to be antagonistic to Aspergillus flavus in stored rice grains. In this study, the biocontrol activities of these strains were evaluated against Aspergillus candidus, Aspergillus fumigatus, Penicillium fellutanum, and Penicillium islandicum, which are predominant in stored rice grains. In vitro and in vivo antifungal activities of the bacterial strains were evaluated against the fungi on media and rice grains, respectively. The antifungal activities of the volatiles produced by the strains against fungal development and population were also tested using I-plates. In in vitro tests, the strains produced secondary metabolites capable of reducing conidial germination, germ-tube elongation, and mycelial growth of all the tested fungi. In in vivo tests, the strains significantly inhibited the fungal growth in rice grains. Additionally, in I-plate tests, strains KU143 and AS15 produced volatiles that significantly inhibited not only mycelial growth, sporulation, and conidial germination of the fungi on media but also fungal populations on rice grains. GC-MS analysis of the volatiles by strains KU143 and AS15 identified 12 and 17 compounds, respectively. Among these, the antifungal compound, 5-methyl-2-phenyl-1H-indole, was produced by strain KU143 and the antimicrobial compounds, 2-butyl 1-octanal, dimethyl disulfide, 2-isopropyl-5-methyl-1-heptanol, and 4-trifluoroacetoxyhexadecane, were produced by strain AS15. These results suggest that the tested strains producing extracellular metabolites and/or volatiles may have a broad spectrum of antifungal activities against the grain fungi. In particular, B. megaterium KU143 and P. protegens AS15 may be potential biocontrol agents against Aspergillus and Penicillium spp. during rice grain storage.